The Development and Dissemination of Pro-Environmental Dharma among Taiwan’s Humanistic Buddhists - Teresa Zimmerman-Liu (Religions, 2023)
In the early 1990s, two of Taiwan’s humanistic Buddhist groups—Buddhist Tzu Chi Compassionate Relief Foundation (Tzu Chi) and Dharma Drum Mountain (DDM)—began incorporating modern environmentalism as a major component in their religious teachings, practices, and behavioral norms. Neither group had been clearly pro-environmental before the 1990s, but Venerable Cheng Yen, the founding master of Tzu Chi, and Venerable Sheng Yen, the founding master of DDM, redefined and expanded Buddhist teachings and practices to include modern concepts and practices of environmental sustainability as central components of their dharmas. This comparative ethnographic study contributes to scholarship with findings regarding how and why the two groups developed and disseminated pro-environmental dharma: (1) both groups began promoting environmentalism as a moral, religious response to Taiwan’s waste management crisis of the early 1990s; (2) both groups tied their pro-environmental teachings to two of the most popular elements of Buddhist dharma among Chinese humanistic Buddhists—the bodhisattva path and pure land teachings; (3) both groups fully integrated environmental teachings, practices, and behavioral norms into all aspects of their organizations; and (4) both groups adjusted the framing of their pro-environmental messages to match specific audiences in their work in order to promote environmentalism in Taiwan’s society.